MTsN 1 Banda Aceh لترقية قدرة الطلبة على فهم الصرف بـــ Fitur Quis Instagram استخدام (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2026)
At MTsN 1 Banda Aceh, researchers found several problems, namely students are difficult to distinguish the changing forms of Fiil Madhi because the teacher conducts the learning process using the lecture method, and the media used is not in accordance with the times. Based on the above problems, researchers are interested in using the Instagram quiz feature to improve students' Sharaf skills. The purpose of this study was to determine the effectiveness of using the Instagram Quiz Feature to improve students' Sharaf skills, and to find out how students respond to the use of the Instagram Quiz Feature at MTsN 1 Banda Aceh. This research uses Experimental method, Quasi Experimental Design (Non Equivalent Pre Test-Post Test Design). In collecting data, researchers used tests and questionnaires. The population in this thesis is MTsN class II students totaling 417 students, and the sample is class II (1) totaling 37 students, and class II (3) totaling 37 people. The researcher will test the results in the form of normal test, homogeneous test and t-test using SPSS 29. The result of this study is the use of Instagram Quiz Feature is effective to improve students' sharaf skills at MTsN 1 Banda Aceh. This result is clearly seen from the Mann-Whitney Test in Table No (5) that the significance level (sig) of 0.000 is smaller than 0.05. Similarly, the results of students' responses to the use of Instagram Quiz Feature media 82.96 with a good category, the evidence can be seen in Table No (6).
Keywords: Instagram Quiz Feature, Sharaf Comprehension.